Actividad reproductiva en Vanzosaura rubricauda (Sauria: teiidae) del Chaco occidental en Argentina - Cruz, Félix B. (1994)
A population of Vanzosaura rubricauda was studied. The exemplars came from the locality of J.V. González, Anta Department, Salta Province. Sexual dichromatism and dimorphism was observed, being males colored on throat region and with a head wider than females, but the later were larger in body size. The population activity was year round, but during the dry and cold months it dropped. Clutch size was constant (2 eggs). Cyclic reproduction was observed, and the major reproductive activity was given in early spring through summer.